New records of scleractinian cold-water coral (CWC) assemblages in the southern Tyrrhenian Sea (western Mediterranean Sea): Human impacts and conservation prospects. (September 2021) - Angiolillo, Michela; La Mesa, Gabriele; Giusti, Michela; Salvati, Eva; Di Lorenzo, Bianca; Rossi, Lorenzo; Canese, Simonepietro; Tunesi, Leonardo
Highlights: Scleractinian CWCs were discovered through ROV imaging in the southern Tyrrhenian Sea. Healthy coral patches were observed on a seamount and bank at depths of 240–310 m. Sparse and dense coral colonies were found dwelling on rocky outcrops and on a wreck. Longline fishing activities have direct and significant impacts on CWC communities. The establishment of an offshore Natura 2000 site (Habitat 1170) is proposed. Abstract: Scleractinian cold-water corals (CWCs) are among the main habitat engineers of the deep Mediterranean Sea, hosting a high diversity of species and playing a significant ecological role. In the last two decades, many new living scleractinian CWC sites throughout the Mediterranean Basin have been recorded and their distribution has been updated. In the summer of 2018, new scleractinian CWC assemblages were discovered by means of remotely operated vehicle (ROV) and multibeam echosounder (MBES) surveys on the Aceste–Tiberio seamount and Marettimo bank in the southern Tyrrhenian Sea, at depths ranging from 240 to 310 m. In the explored areas, megabenthic communities were dominated by habitat-forming species, some of which have never been reported before on these submarine structures. Healthy patches of Madrepora oculata and Desmophyllum pertusum, together with the solitary coral D. dianthus, were found on rocky pinnacles between inclined silted bottoms, as well as on a wreck. Deep-water fishing activities, mainly longline fishing, negatively affected these communities, particularly coral species. The discovery of these new sites adds new knowledge about the distribution of scleractinian CWCs in the Mediterranean Sea. Moreover, the documented negative effect of fishing activities on CWC species further stresses the need for urgent and specific conservation measures. In this regard, the co-occurrence of several long-lived, slow-growing, and vulnerable species on these seamounts and banks supports the establishment of specific marine protected areas [i.e., offshore Natura 2000 sites, in accordance with the Habitats Directive (92/43/EEC) - Habitat 1170 - Reefs].